Participatory practice guideline development at the intersections of domestic and family violence, mental distress and/or parental substance use. Issue 1 (16th February 2022) - Heward-Belle, Susan Lynn; Kertesz, Margaret; Humphreys, Cathy; Tsantefski, Menka; Isobe, Jasmin
Abstract : Purpose: It is well established that the service system has a poor history of responding holistically to address the needs of children and families living with co-occurring complexities such as domestic violence, parental mental health and/or substance use. The purpose of this conceptual paper is to primarily describe the developmental process used to create guidelines to inform practice at the intersections of domestic violence, mental health and alcohol and other drug services, ensuring that the tactics of coercive control are visible in contexts of complexity. Design/methodology/approach: The guidelines were developed through undertaking a literature review, followed by a practice-led research approach with practitioners from 33 organisations across three Australian states, Safe & Together consultants and researchers. Communities of practice composed of practitioners providing interventions to children and families were central to the approach. Data that informed the development of the guidelines included a literature review, ethnographic notes, qualitative interviews, quantitative surveys and reflections. Findings: Practice-led research engaged practitioners in the development of guidelines to promote an integrated response to working with families experiencing domestic violence, substance use and mental health issues. The integrated approach drew from the Safe & Together model, emphasising partnering with women survivors, pivoting to the perpetrator, focusing on children's safety and well-being, promoting worker safety, collaborating across agencies and influencing organisational change. The process demonstrated the usefulness of this integrated approach, using practitioner-based examples. Originality/value: Successful iterative processes to develop the guidelines were undertaken to support cultural change towards holistic and collaborative work across multiple sectors and organisations.